Injected Hyaluronidase Reduces the Volume of Exogenous Hyaluronate Fillers in Mice and Results in Clinical Improvement in a Patient with Pretibial Myxedema - Sébastien Menzinger; Aysin Kaya; Jean-Hilaire Saurat; Gürkan Kaya (MDPI AG, 2016)
Background: Hyaluronidases are essential for the breakdown of hyaluronate (HA) in tissues and may be used to prevent the adverse effects of HA fillers. Objectives: We explored the effect of hyaluronidase on exogenous and endogenous HA in vitro and in vivo. Materials and Methods: HA fillers were incubated with different concentrations of hyaluronidase and visualized by electrophoresis. HA fillers were injected in the skin of hairless mice, and 4 h later hyaluronidase was injected in the papules of exogenous HA. Hyaluronidase was injected in the nodule of pretibial myxedema of a male patient with Graves' disease. Skin sections of mice and of the patient were performed, and a skin ultrasound system was used to monitor the evolution of skin lesions. Results: Hyaluronidase showed a degrading effect on HA with increasing concentrations. Hyaluronidase injection significantly decreased the content of exogenous HA within 3 days. Intralesional injection of hyaluronidase resulted in dissolution of the nodule of pretibial myxedema with no recurrence during 3 months. Conclusion. These results show that the injection of hyaluronidase is capable of degrading exogenous HA in mouse skin and endogenous HA in human skin in vivo and may be a therapeutic option for skin diseases characterized by abnormal accumulation of HA.